Genetic polymorphisms of interleukin-4 third intron region in the Malaysian patients with systemic lupus erythematosus - Chua, K.H.; Pin, K.B.; Yen, T.S.; Hoong, L.L. (Asian Network for Scientific Information, 2008)
In this study, we analysed the genetic polymorphisms present in the third intron region of Interleukin-4 gene in Malaysian patients with Systemic Lupus Erythematosus. Overall, the RP I and II alleles were found evenly distributed in both the SLE patients and control individuals. There was no significant association observed in the distribution of allelic and genotypic frequencies between SLE patients and healthy controls. The result obtained is similar to a previous study carried out on SLE Chinese patients in Taiwan.